1991
DOI: 10.1038/349526a0
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of Mls genes to endogenous mammary tumour viruses of inbred mice

Abstract: T cells that recognize self antigen are clonally deleted in the thymus--a maturation process that occurs in the context of histocompatibility molecules and the T-cell receptor. The minor lymphocyte stimulation antigens (Mls) effect these deletions through interactions with the V beta portion of the T-cell receptor, thus mimicking bacterial 'superantigens'. Intrigued by the fact that each known Mls gene maps to the same chromosomal region as an endogenous mouse mammary tumour virus (Mtv), we reevaluated the lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
146
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 296 publications
(149 citation statements)
references
References 35 publications
2
146
1
Order By: Relevance
“…Expression of superantigens encoded by mouse mammary tumor viruses leads to I-E-dependent deletion of double-positive thymocytes bearing V␤5, 11, and 12 in B10.BR mice (27), and can be used as a model for negative selection. CD4 ϩ SP thymocytes from WT B10.BR and SHP2(CS) B10.BR mice were assessed for expression of V␤5, 11, and 12.…”
Section: T Cell Development In Shp2(cs) Micementioning
confidence: 99%
“…Expression of superantigens encoded by mouse mammary tumor viruses leads to I-E-dependent deletion of double-positive thymocytes bearing V␤5, 11, and 12 in B10.BR mice (27), and can be used as a model for negative selection. CD4 ϩ SP thymocytes from WT B10.BR and SHP2(CS) B10.BR mice were assessed for expression of V␤5, 11, and 12.…”
Section: T Cell Development In Shp2(cs) Micementioning
confidence: 99%
“…Specific endogenous MMTV loci segregate with the deletion of certain specific classes of Tcells during the establishment of tolerance (Table 1) (Dyson et al, 1991;Frankel et al, 1991;Marrack et al, 1991 ;Woodland et al, 1991 a Janeway, 1991;Palmer, 1991 (Choi et al, 1991) in an in vitro assay. In the transgenic mouse study, the relevant T-lymphocyte subclass is deleted in response to the newly introduced superantigen , albeit at a slower rate than has been observed for normal endogenous Mls antigens.…”
Section: Mmtv and Superantigensmentioning
confidence: 99%
“…Retroviral superantigens were first depicted in the B-type virus group in mouse mammary tumor viruses and are found in both infectious mouse mammary tumor viruses and endogenous proviruses (14,18,39,63). It has been previously shown that the env gene of HERV-K18, a defective human endogenous provirus located on chromosome 1, encodes a superantigen activity (51,52).…”
mentioning
confidence: 99%